PENERAPAN SISTEM HYBRID FREEZER PALKA PANEL SURYA DAN MESIN UNTUK MENUNJANG PRODUKTIVITAS NELAYAN - yusuf, muhammad; rofiq, Ainur; Jusef Saiful; Ananta Kusuma Yoga Pratama (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2025)
Traditional fishermen in coastal communities often rely on ice blocks to preserve their catch, a method that is costly, inefficient, and unable to maintain stable temperatures during long fishing trips. This study presents the development and implementation of a hybrid freezer palka system that integrates solar panels and engine-driven alternator power to provide a continuous and energy-efficient cooling source for small fishing vessels. The research aimed to design a reliable cooling system capable of maintaining low temperatures during extended operations at sea while reducing operational costs for fishermen.The methodology involved system design, component integration, and field testing with partner fishermen in Kampung Mandar, Banyuwangi. The hybrid system consists of a 100 Wp solar panel, MPPT charge controller, 65 Ah battery, alternator, inverter, and a 125-Watt freezer installed inside an insulated palka box. Field testing was conducted over 21 consecutive days to evaluate temperature stability, operating duration, and energy performance.Results show that the system successfully reached temperatures between –2 °C and 5 °C within approximately 80 minutes and maintained stable cooling for more than 8 hours per trip using combined solar and engine power. The hybrid configuration significantly reduced dependence on ice blocks, decreased operational costs, and improved fish quality upon landing. The findings indicate that this hybrid freezer palka system is an effective, sustainable, and practical technological solution to support fishermen’s productivity, especially in small-scale traditional fisheries..